CORRECTING STUDENTS’ MISCONCEPTION IN ACID AND BASE CONCEPT USING PDEODE INSTRUCTION STRATEGY - Lathifa, Ulya (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
This study aimed (1) to calculate the percentage of students who understand concepts, having misconceptions, and don’t understand concepts, (2) to identify students’ misconceptions of acid and base concept, and (3) to test the effectiveness of PDEODE (Predict-Discuss-Explain-Observe-Discuss-Explain) instruction strategy in correcting students’ misconceptions of acid and base concept. This research uses descriptive and pre-experimental one-group pretest-posttest design. The sample consisted of 37 students of 11th grade IPA 4 MAN 1 Kudus. The misconceptions are identified using modified CRI (Certainty of Response Index) techniques and explored through semistructured interviews to get deep informations. The effectiveness of PDEODE instruction strategy was determined from the analysis of paired samples t-test. The results of this study are: (1) the level of students’ misconception of acid and base concept changed significantly after was repaired by PDEODE instruction strategy and (2) there were 45 kinds of students’ misconceptions of the subconcepts: characteristics of acids and bases, acid and base theories, strength of acid and base, neutralization reaction, and pH of solution